Bouma Studio: A Web Solution for Encapsulated Moments in Motion - Razak, Farisha Qistina; Jaafar, Juliana (Journal of Computing Technologies and Creative Content, 2025)
The web application, Bouma Studio, aims to over- come the challenges of service management for its potential customers by providing a seamless platform to access package information and prices, browse the photography portfolio, book packages, and receive updates about quotations and invoices. Key challenges identified include inefficient reservation processes, reliance on studio admin efforts to find freelancers online, and difficulty for customers in accessing Bouma Studio’s information, leading to missed reservations. To address these issues, the project involved studying customer and administrator requirements, designing, and implementing a web application using an iterative model. The methodology included interviews with the three di- rectors of Bouma Studio and 19 previous and potential customers for context analysis, followed by evaluations using questionnaires and interviews. The findings show that the system significantly reduced the time spent searching for online photographers by 83.52%, improved access to package information by 90%, and enhanced the efficiency of receiving quotations and invoices by 100%, resulting in an improved overall booking experience.